Carrion's disease (Bartonellosis Humana) . Morphological study of the blood count and the previous eruptive phase with the Electronic Microscopy - Takano Morón, Juan (1970)
In Carrion 's disease (human Bartonellosis ) described two phases: 1 ) Phase blood count and 2 ) Phase histíoide . In Phase hematic recently been shown that the Bartonella bacilliformis etiolóqico Disease agent is located within the host erythrocyte . 1) pre - eruptive period and 2 ) Eruptive Period or verrucous outbreak : In Phase histioide two periods described . The histological picture of verrucous button is a capillary hemangioma granuloma or a pióqeno : however, sometimes the differential diagnosis with other entities , especially malignancies, is difficult. Special staining techniques , it has been observed in the cytoplasm of cells verrucoma histioides small granules have been considered baciliformis form . In this paper discloses the results of the ultrastructural study of Bartonella - complex and RBC verrucoma for which thin sections were used coagulated blood, desfibringda blood, hemolyzed erythrocytes and no flowery verrucomas complicated . It states that there are three forms of B. bacilliformis classically described in erythrocytes , ie , bacillary forms and coccoid in coccobacillary verrucoma , whereas the latter form , from the point of view ultrastructural is predominantly oval . The B. bacilliformis , in erythrocytes , has the characteristics of thick-walled bacteria as described in gram- poitivos ; however, the verrucoma B. bacilliiormis being ultrastructurally similar bacterial wall is thin , difference is discussed in terms of their possible significance . On the other hand , the different forms of the verrucoma baciliformis are smaller than their counterparts of the erythrocyte , considering that this difference may be artificial , under more or less retraction of the tissues to the active re used in the preparation of inclusions for obtaining thin sections . For observations follows that Ia B. bacilliformis is incorporated within the red blood cell by pinocifosis . This germ multiplies in the red blood cells and in the cytoplasm of some cells by cross verrucoma full Septation . The flowery verrucoma consists not complicated by several types of cells probably originate from the most primitive cell ; three of them, which include endothelial cells , have the capacity to engulf bartonellae being exerted on the macrophage phagocytic activity increased . Among the cellular elements of verrucoma "fundamental substance " , cellular debris , fibers and bartonellae colóceno . Observed The macrophage is characterized by verrucoma few lisomas made ​​is discussed in relation to the characteristics of B. bacilliformis Verrucoma complex . In light of the ultrastructural observations of the blood count and the previous eruptive phase of Carrion's disease , some considerations on the host-parasite relationship and the projection that these findings may have on understanding the immune mechanism of this infectious process are .